Reforestation Impact: Contrasting Carbon Stock and Biodiversity of Clove in Monoculture and Mixed Gardens Over 25 Years - Avianto, Yovi; Noviyanto, Amir; Sidiq, Muhamad Fajar; Hernowo, Hernowo; Pratama, Ananta Bayu (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Tropical forests, vital for absorbing CO2 and maintaining ecosystem balance, are threatened by deforestation and unsustainable agricultural practices. Mixed garden or clove agroforestry systems, which combine clove cultivation with other crops, offer a sustainable alternative to traditional monoculture practices. This study aims to assess the biomass potential, carbon storage, and biodiversity in clove monoculture and mixed garden systems. The research was conducted in February 2024 at smallholder clove plantations and secondary forests in Pesaren, Sukorejo, Kendal, Central Java. The study involved primary data collection on clove monoculture and mixed garden systems using standardized plot sampling techniques. Biomass, carbon storage and carbon sequestration was calculated through field measurements utilizing allometric equations, while biodiversity was assessed using the Shannon-Wiener index based on species richness and evenness within the sampled plots. The mixed garden system closely approximates secondary forests in terms of biomass, carbon storage, CO2 sequestration, biodiversity, and species evenness, with respective values of 100.36 tons/ha, 47.17 tons/ha, 173.11 tons/ha, 2.837, and 0.91. In contrast, the clove monoculture system recorded the lowest values across all parameters: 67.03 tons/ha for biomass, 31.50 tons/ha for carbon storage, and 115.61 tons/ha for CO2 sequestration, with a dominance of one species and a Shannon-Wiener index and evenness value of 0. These results highlight the superior ecological benefits of mixed garden systems over monoculture clove plantations.